SnTe-based thermoelectric material and preparation method thereof
By doping SnTe with tungsten and combining it with In2Te3 and Cu2Te, the thermoelectric performance of SnTe-based materials is enhanced by breaking the coupling between Seebeck coefficient and electrical conductivity, leading to a significant increase in ZT value and efficiency.
Patent Information
- Application Number
- CN202510482156.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-07-08
- Estimated Expiration
- 2045-04-17
AI Technical Summary
SnTe-based thermoelectric materials face challenges in achieving high thermoelectric figure of merit (ZT) due to strong coupling between Seebeck coefficient and electrical conductivity, limited by high concentrations of native Sn vacancies and low Seebeck coefficient, which are not effectively addressed by existing strategies.
A novel approach involving the doping of SnTe with tungsten (W) and combining it with In2Te3 and Cu2Te to form Sn2.9-XWXTe2.9-(In2Te3)0.03-(Cu2Te)0.18, which introduces gap defects and additional conductive pathways, enhancing power factor and reducing lattice thermal conductivity through nano-scale interfaces and structural defects.
This method significantly improves the thermoelectric performance of SnTe-based materials by breaking the coupling between Seebeck coefficient and electrical conductivity, resulting in a substantial increase in ZT value and overall efficiency.
Smart Images

Figure CN120282700A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of thermoelectric technology, and particularly to a SnTe-based thermoelectric material and a preparation method thereof. Background Art
[0002] As a means capable of directly converting thermal energy into electrical energy or creating a temperature difference through electrical energy in reverse, thermoelectric technology has gradually become a research hotspot because it can effectively utilize various waste heat resources, such as industrial waste heat and solar energy. Compared with traditional power generation methods, thermoelectric technology not only reduces the dependence on fossil fuels but also improves energy utilization efficiency, contributing to emissions reduction and environmental protection.
[0003] Thermoelectric materials, with their efficient, environmentally friendly, and flexible characteristics, have shown extensive application potential. For example, in the aerospace field, thermoelectric devices can meet the demand for efficient energy conversion and improve the energy utilization efficiency of spacecraft; in medical devices, thermoelectric materials can be used in noiseless and precise body temperature monitoring devices; in the microelectronics field, thermoelectric materials can provide stable power support for microelectronic devices. With the continuous improvement of the performance of thermoelectric materials, they will play a more important role in energy conversion, environmental protection, etc., and become one of the key technologies to address global energy challenges. The conversion efficiency of thermoelectric materials is usually quantified by the thermoelectric figure of merit ZT, and its formula is ZT = S 2 σT / (κ e +κ lat ), where S represents the Seebeck coefficient, σ is the electrical conductivity, T is the absolute temperature, κ e and κ lat represent the carrier thermal conductivity and the lattice thermal conductivity respectively. The key to improving the ZT value lies in increasing the Seebeck coefficient while reducing the lattice thermal conductivity of the material. However, the mutual coupling relationship among S, σ, and κ e poses a challenge to achieving a high ZT value. Therefore, decoupling these three is the core of improving the ZT value.
[0004] SnTe-based thermoelectric materials have become an ideal choice for medium-temperature thermoelectric materials due to their non-toxicity and ease of synthesis. As an analogue of PbTe, environmentally friendly SnTe shows broad application prospects in large-scale commercial power generation. However, due to the relatively large number of intrinsic Sn vacancies in SnTe, it leads to a high concentration of hole carriers, a low Seebeck coefficient, and a high carrier thermal conductivity, which limits its thermoelectric performance. Currently, various strategies have been successfully applied to optimize the thermoelectric performance of SnTe. For example, by substituting cations at the Sn position (such as doping elements like Mn, Bi, Sr, and In), the energy band structure of SnTe (such as valence band convergence) can be improved, thereby significantly increasing the Seebeck coefficient, but this usually reduces the electrical conductivity. Due to the strong coupling relationship between the Seebeck coefficient and the electrical conductivity, it is impossible to achieve a high thermoelectric figure of merit.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the Invention
[0006] In view of the deficiencies of the above prior art, the purpose of the present invention is to provide a SnTe-based thermoelectric material and its preparation method, aiming to solve the problems that the existing SnTe-based thermoelectric materials cannot achieve a high thermoelectric figure of merit and have low thermoelectric performance.
[0007] The technical solution of the present invention is as follows: In the first aspect of the present invention, a preparation method of a SnTe-based thermoelectric material is provided, wherein the SnTe-based thermoelectric material is composed of tungsten-doped SnTe and In2Te3, Cu2Te composites, and the SnTe-based thermoelectric material is denoted as Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 , x = 0 to 0.15, and x does not take 0; The preparation method of the SnTe-based thermoelectric material includes the steps of: S1. In an inert gas environment, according to the stoichiometric ratio of the chemical formula Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 , mix elemental Te, elemental Sn, elemental In, elemental Cu and elemental W to obtain a mixed raw material, and perform vacuum encapsulation on the mixed raw material; S2. Perform a melting reaction on the vacuum-encapsulated mixed raw material to obtain an ingot, and perform annealing treatment on the ingot; S3. After grinding the annealed ingot into powder, perform spark plasma sintering to obtain a SnTe-based thermoelectric material.
[0008] Optionally, in step S1, the purity of the elemental Te, the purity of the elemental Sn, the purity of the elemental In, the purity of the elemental Cu and the purity of the elemental W are respectively greater than or equal to 99.999%; The step of performing vacuum encapsulation on the mixed raw material specifically includes: transferring the mixed raw material into a quartz tube, and encapsulating the quartz tube by using a hydrogen-oxygen flame in a vacuum environment.
[0009] Optionally, in step S2, the process conditions of the melting reaction include: heating the quartz tube from room temperature to 1200 - 1300K within 6 - 8 hours, and holding for 8 - 12 hours; after the holding is completed, quench the quartz tube in supersaturated salt water at room temperature.
[0010] Optionally, the process conditions for the melting reaction are as follows: within 8 hours, heat the quartz tube from room temperature to 1273 K and keep it at this temperature for 10 hours; after the heat preservation, quench the quartz tube in supersaturated salt water at room temperature.
[0011] Optionally, in step S2, the process conditions for the annealing treatment include: heat the ingot to 923 - 975 K within 4 - 6 hours, keep it at this temperature for 1 - 3 days, and then cool it to room temperature.
[0012] Optionally, the process conditions for the annealing treatment are as follows: heat the ingot to 950 K within 6 hours, keep it at this temperature for 3 days, and then cool it to room temperature.
[0013] Optionally, in step S3, the process conditions for the spark plasma sintering include: in a vacuum environment, sinter at a temperature range of 600 - 700 K and a pressure of 50 - 60 MPa, and the sintering time is 5 - 10 minutes.
[0014] Optionally, the process conditions for the spark plasma sintering are as follows: in a vacuum environment, sinter at a temperature of 673 K and a pressure of 52 MPa, and the sintering time is 10 minutes.
[0015] In the second aspect of the present invention, a SnTe - based thermoelectric material is provided, wherein the SnTe - based thermoelectric material is prepared by using the preparation method of the SnTe - based thermoelectric material of the present invention.
[0016] In the third aspect of the present invention, a SnTe - based thermoelectric material is provided, wherein the SnTe - based thermoelectric material is composed of tungsten - doped SnTe, In2Te3, and Cu2Te, and the SnTe - based thermoelectric material is denoted as Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 , where x = 0 - 0.15 and x does not take the value of 0.
[0017] Beneficial effects: In the present invention, tungsten (W) interstitial defects are introduced into SnTe, and at the same time, it is compounded with In2Te3 and Cu2Te. A new doping - compounding method effectively relieves the strong coupling relationship between the Seebeck coefficient and the conductivity, thereby improving the power factor and effectively reducing the lattice thermal conductivity, achieving a high thermoelectric figure of merit. Specifically: The W interstitial defects caused by alloying W with SnTe can effectively reduce the formation energy of intrinsic Sn vacancy defects; the introduced In2Te3 and Cu2Te composite phases provide additional conductive channels for carriers and enhance the migration ability of carriers. Under the combined action of the two, the conductivity of the SnTe - based thermoelectric material is improved. In addition, the energy band convergence and energy band flattening effects, as well as the introduction of a large number of nano - precipitates, bring a large number of interfaces and structural defects. These interfaces strongly scatter low - energy phonons, thereby reducing bipolar diffusion and further increasing the Seebeck coefficient. In addition, a large number of interfaces are formed by introducing composite phases in the form of nano - precipitates. These interfaces enhance phonon scattering, and the interface scattering brought by this composite phase will significantly reduce the carrier thermal conductivity; the lattice distortion of excessive W is significantly exacerbated. Excessive W atoms introduce a large number of defects and impurities in the lattice, which leads to a significant enhancement of phonon scattering. The lattice defects and possible impurity phases (such as W - rich phases) together bring an enhancement of phonon - phonon scattering and phonon - defect scattering, significantly reducing the lattice thermal conductivity. Finally, the thermoelectric figure of merit of the SnTe - based thermoelectric material is greatly improved, thereby enhancing the thermoelectric performance of the SnTe - based thermoelectric material. The preparation process of the SnTe - based thermoelectric material of the present invention is simple and has a short preparation period. Brief Description of the Drawings
[0018] Figure 1 XRD diagrams of Sn thermoelectric materials with different W concentrations and two - metal - compound composites in Examples 1 - 6 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 XRD diagrams of the thermoelectric materials of Sn with different W concentrations and two - metal - compound composites in Examples 1 - 6 and the SnTe thermoelectric material of Comparative Example 1; Figure 2 XRD diagrams of Sn thermoelectric materials with different W concentrations and two - metal - compound composites in Examples 1 - 6 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Graph of the conductivity - temperature dependence of the thermoelectric materials of Sn with different W concentrations and two - metal - compound composites in Examples 1 - 6 and the SnTe thermoelectric material of Comparative Example 1; Figure 3 XRD diagrams of Sn thermoelectric materials with different W concentrations and two - metal - compound composites in Examples 1 - 6 2.9-X W X Te 2.9-(In2Te3) 0.03 -(Cu2Te) 0.18 Curves of the Seebeck coefficient versus temperature for the thermoelectric material and the SnTe thermoelectric material of Comparative Example 1; Figure 4 For Sn with different W concentrations in Examples 1-6 and the composite of two metal compounds 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Curves of the power factor versus temperature for the thermoelectric material and the SnTe thermoelectric material of Comparative Example 1; Figure 5 For Sn in Example 5 2.78 W 0.12 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Transmission electron microscope photograph of the thermoelectric material; Figure 6 For Sn with different W concentrations in Examples 1-6 and the composite of two metal compounds 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Curves of the total thermal conductivity versus temperature for the thermoelectric material and the SnTe thermoelectric material of Comparative Example 1; Figure 7 For Sn with different W concentrations in Examples 1-6 and the composite of two metal compounds 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Curves of the ZT value versus temperature for the thermoelectric material and the SnTe thermoelectric material of Comparative Example 1; Figure 8 For Sn with different W concentrations in Examples 1-6 and the composite of two metal compounds 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Bar graph of the average ZT value versus the W concentration for the thermoelectric material and the SnTe thermoelectric material of Comparative Example 1. Detailed implementation manners
[0019] The present invention provides a SnTe-based thermoelectric material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0020] In one embodiment, a method for preparing a SnTe-based thermoelectric material is provided, wherein the SnTe-based thermoelectric material is composited with tungsten-doped SnTe and In2Te3 and Cu2Te, and the SnTe-based thermoelectric material is denoted as Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 , x=0~0.15, and x is not 0; The method for preparing the SnTe-based thermoelectric material comprises the steps of: S1. In an inert gas environment, according to the chemical formula Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Mixing Te, Sn, In, Cu and W in a stoichiometric ratio to obtain a mixed raw material, and vacuum packaging the mixed raw material, wherein x=0-0.15, and x is not 0; S2, subjecting the vacuum-encapsulated mixed raw materials to a melting reaction to obtain an ingot, and subjecting the ingot to an annealing treatment; S3, grinding the annealed ingot into powder, and then performing spark plasma sintering to obtain SnTe-based thermoelectric material.
[0021] In the preparation process of this embodiment, high-purity metal elements are used as raw materials and mixed according to the stoichiometric ratio. The metal elements are mixed and vacuum-sealed, and then the ingots are melted and reacted to obtain ingots. The ingots are then annealed at high temperature. After the ingots are ground into powder, spark plasma sintering (SPS) is used to form dense bulk SnTe-based thermoelectric materials. The chemical formula of the SnTe-based thermoelectric material is Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 In this embodiment, tungsten (W) element is doped into the SnTe matrix and compounded with two metal compounds, In2Te3 and Cu2Te, thereby significantly improving the thermoelectric figure of merit of the SnTe-based thermoelectric material and improving the thermoelectric performance of the SnTe-based thermoelectric material.
[0022] Specifically, by introducing W element into SnTe, W defects are introduced into the lattice interstitial sites, thereby improving the electrical transport performance; introducing In2Te3 and Cu2Te composite phases can provide additional conductive channels and reduce bipolar diffusion, thus improving the electrical transport performance. At the same time, the interstitial defects and lattice distortion brought by tungsten doping; the composite phases are introduced in the form of nano-precipitates to form a large number of interfaces, enhancing phonon scattering. Through this combined strategy, the lattice thermal conductivity is significantly reduced. Therefore, this method effectively improves the thermoelectric figure of merit of SnTe-based thermoelectric materials, thereby enhancing the thermoelectric performance of SnTe-based thermoelectric materials.
[0023] In one embodiment, in step S1, the purities of the Te single element, Sn single element, In single element, Cu single element, and W single element are respectively greater than or equal to 99.999%. The step of vacuum encapsulating the mixed raw materials specifically includes: transferring the mixed raw materials into a quartz tube and encapsulating the quartz tube using a hydrogen-oxygen flame under a vacuum environment.
[0024] In one embodiment, in step S2, the process conditions of the melting reaction include: slowly heating the quartz tube from room temperature to 1200 - 1300K within 6 - 8 hours, and holding for 8 - 12 hours to ensure that the raw materials are fully melted and reacted completely; after the holding is completed, quenching the quartz tube in supersaturated brine at room temperature.
[0025] In one embodiment, the process conditions of the melting reaction are: slowly heating the quartz tube from room temperature to 1273K within 8 hours and holding for 10 hours; after the holding is completed, quenching the quartz tube in supersaturated brine at room temperature.
[0026] In one embodiment, in step S2, the process conditions of the annealing treatment include: heating the ingot to 923 - 975K within 4 - 6 hours, holding for 1 - 3 days, and then slowly cooling to room temperature.
[0027] In one embodiment, the process conditions of the annealing treatment are: heating the ingot to 950K within 6 hours, holding for 3 days, and then slowly cooling to room temperature.
[0028] In one embodiment, in step S3, the process conditions of the spark plasma sintering include: sintering under a vacuum environment within a temperature range of 600 - 700K and at a pressure of 50 - 60MPa, and the sintering time is 5 - 10 minutes. Sintering under these temperature and pressure conditions can ensure the densification of the product, and finally obtain a high-density bulk SnTe-based thermoelectric material.
[0029] In one embodiment, the process conditions for spark plasma sintering are as follows: in a vacuum environment, at a temperature of 673K and a pressure of 52MPa, and the sintering time is 10 minutes. Sintering under these temperature and pressure conditions can further improve the density of the product.
[0030] In one embodiment, a SnTe-based thermoelectric material is provided, wherein the SnTe-based thermoelectric material is composed of tungsten-doped SnTe and In2Te3, Cu2Te composites, and the SnTe-based thermoelectric material is denoted as Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 , x = 0 to 0.15 (such as 0.03, 0.06, 0.09, 0.12, 0.15, etc.), and x does not take 0; And / or, the SnTe-based thermoelectric material is prepared by using the preparation method of the SnTe-based thermoelectric material described in any one of the above embodiments.
[0031] The present invention will be further described in detail below through specific embodiments.
[0032] Example 1 The Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 preparation method of the thermoelectric material (x = 0) is as follows: S1. In an inert gas environment, according to the chemical formula Sn 2.9 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The stoichiometric ratio of the metal elements Sn, Cu, In, and Te is weighed, and the purity of each metal element is greater than or equal to 99.999%. Subsequently, the metal elements are uniformly mixed and transferred into a quartz tube, and the quartz tube is flame-sealed in a vacuum environment with an absolute vacuum degree less than or equal to 0.1 Pa by using a hydrogen-oxygen machine.
[0033] S2. Under vacuum conditions, the quartz tube after flame-sealing in step S1 is placed in a box furnace, heated from room temperature to 1273K within 8 hours, and kept at this temperature for 10 hours; after the heat preservation is completed, the quartz tube is immediately quenched in cold water to room temperature to obtain an ingot; Under vacuum conditions, the ingot is subjected to high-temperature annealing. The high-temperature annealing process includes: within 6 hours, the quartz tube is heated from room temperature to 950K, kept at this temperature for 3 days, and then cooled to room temperature.
[0034] S3. Grind the ingot after high-temperature annealing in step S2 into powder, and then carry out spark plasma sintering in a vacuum environment at a sintering temperature of 673 K, a pressure of 52 MPa, and a time of 10 minutes to obtain high-density Sn 2.9 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 bulk thermoelectric material.
[0035] Example 2 For the Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The preparation method of the thermoelectric material (x = 0.03) is as follows: S1. In an inert gas environment, weigh the metal elements Sn, Cu, In, and Te according to the stoichiometric ratio of the chemical formula Sn 2.87 W 0.03 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 such that the purity of each metal element is greater than or equal to 99.999%. Subsequently, uniformly mix the metal elements and transfer them to a quartz tube, and then use a hydrogen-oxygen machine to seal the tube in a vacuum environment with an absolute vacuum degree less than or equal to 0.1 Pa.
[0036] S2. Under vacuum conditions, place the quartz tube after flame sealing in step S1 in a box furnace, heat it from room temperature to 1273 K within 8 hours, and hold for 10 hours; after the holding is completed, immediately quench the quartz tube in cold water to room temperature to obtain an ingot; Under vacuum conditions, perform high-temperature annealing on the ingot. The high-temperature annealing process includes: within 6 hours, heat the quartz tube from room temperature to 950 K, hold for 3 days, and then cool to room temperature.
[0037] S3. Grind the ingot after high-temperature annealing in step S2 into powder, and then carry out spark plasma sintering in a vacuum environment at a sintering temperature of 673 K, a pressure of 52 MPa, and a time of 10 minutes to obtain high-density Sn 2.87 W 0.03 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 bulk thermoelectric material.
[0038] Example 3 For the Sn 2.9-X W X Te 2.9-(In2Te3) 0.03 -(Cu2Te) 0.18 The preparation method of the thermoelectric material (x = 0.06) is as follows: S1. In an inert gas environment, according to the chemical formula Sn 2.84 W 0.06 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 weigh the metal elements Sn, Cu, In and Te according to the stoichiometric ratio, the purity of each metal element is greater than or equal to 99.999%, then uniformly mix the metal elements and transfer them into a quartz tube, and use a hydrogen-oxygen machine to seal the tube by flame in a vacuum environment with an absolute vacuum degree less than or equal to 0.1 Pa.
[0039] S2. Under vacuum conditions, place the quartz tube sealed by flame in step S1 into a box furnace, heat it from room temperature to 1273 K within 8 hours, and keep it warm for 10 hours; after the heat preservation is completed, immediately place the quartz tube in cold water and quench it to room temperature to obtain an ingot; Under vacuum conditions, perform high-temperature annealing on the ingot. The high-temperature annealing process includes: within 6 hours, heat the quartz tube from room temperature to 950 K, keep it warm for 3 days, and then cool it to room temperature.
[0040] S3. Grind the ingot annealed at high temperature in step S2 into powder sufficiently, and then perform spark plasma sintering in a vacuum environment. The sintering temperature is 673 K, the pressure is 52 MPa, and the time is 10 minutes, thus obtaining a high-density Sn 2.84 W 0.06 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 bulk thermoelectric material.
[0041] Example 4 The Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The preparation method of the thermoelectric material (x = 0.09) is as follows: S1. In an inert gas environment, according to the chemical formula Sn 2.81 W 0.09 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18Weigh the metallic elements Sn, Cu, In, and Te according to their stoichiometric ratios. The purity of each metallic element is greater than or equal to 99.999%. Subsequently, uniformly mix the metallic elements and transfer them into a quartz tube. Use a hydrogen-oxygen machine to perform flame sealing of the tube in a vacuum environment with an absolute vacuum degree less than or equal to 0.1 Pa.
[0042] S2. Under vacuum conditions, place the quartz tube after flame sealing in step S1 into a box furnace, heat it from room temperature to 1273 K within 8 hours, and hold for 10 hours; after the holding is completed, immediately quench the quartz tube in cold water to room temperature to obtain an ingot. Under vacuum conditions, perform high-temperature annealing on the ingot. The high-temperature annealing process includes: within 6 hours, heat the quartz tube from room temperature to 950 K, hold for 3 days, and then cool it to room temperature.
[0043] S3. Grind the ingot after high-temperature annealing in step S2 into powder, and then perform spark plasma sintering in a vacuum environment at a sintering temperature of 673 K, a pressure of 52 MPa, and a time of 10 minutes to obtain a high-density Sn 2.81 W 0.09 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 bulk thermoelectric material.
[0044] Example 5 The Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The preparation method of the thermoelectric material (x = 0.12) is as follows: S1. In an inert gas environment, weigh the metallic elements Sn 2.78 W 0.12 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 according to their stoichiometric ratios. The purity of each metallic element is greater than or equal to 99.999%. Subsequently, uniformly mix the metallic elements and transfer them into a quartz tube. Use a hydrogen-oxygen machine to perform flame sealing of the tube in a vacuum environment with an absolute vacuum degree less than or equal to 0.1 Pa.
[0045] S2. Under vacuum conditions, place the quartz tube after flame sealing in step S1 into a box furnace, heat it from room temperature to 1273 K within 8 hours, and hold for 10 hours; after the holding is completed, immediately quench the quartz tube in cold water to room temperature to obtain an ingot. Under vacuum conditions, the ingot is subjected to high-temperature annealing. The high-temperature annealing process includes: raising the temperature of the quartz tube from room temperature to 950 K within 6 hours, holding for 3 days, and then cooling to room temperature.
[0046] S3. Grind the ingot after high-temperature annealing in step S2 into powder sufficiently, and then perform spark plasma sintering in a vacuum environment at a sintering temperature of 673 K, a pressure of 52 MPa, and a time of 10 minutes to obtain high-density Sn 2.78 W 0.12 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 bulk thermoelectric material.
[0047] Example 6 The Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The preparation method of the thermoelectric material (x = 0.15) is as follows: S1. In an inert gas environment, weigh the metal elements Sn 2.75 W 0.15 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 according to the stoichiometric ratio, with the purity of each metal element being greater than or equal to 99.999%. Subsequently, uniformly mix the metal elements and transfer them into a quartz tube, and perform flame sealing of the tube in a vacuum environment with an absolute vacuum degree less than or equal to 0.1 Pa using a hydrogen-oxygen machine.
[0048] S2. Under vacuum conditions, place the quartz tube after flame sealing in step S1 into a box furnace, raise the temperature from room temperature to 1273 K within 8 hours, and hold for 10 hours; after the holding ends, immediately quench the quartz tube in cold water to room temperature to obtain an ingot; Under vacuum conditions, the ingot is subjected to high-temperature annealing. The high-temperature annealing process includes: raising the temperature of the quartz tube from room temperature to 950 K within 6 hours, holding for 3 days, and then cooling to room temperature.
[0049] S3. Grind the ingot after high-temperature annealing in step S2 into powder sufficiently, and then perform spark plasma sintering in a vacuum environment at a sintering temperature of 673 K, a pressure of 52 MPa, and a time of 10 minutes to obtain high-density Sn 2.75 W 0.15 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18Bulk thermoelectric material.
[0050] Comparative Example 1 The preparation method of the SnTe thermoelectric material in this comparative example is as follows: S1. In an inert gas environment, metallic elements Sn and Te are weighed according to the stoichiometric ratio of the chemical formula SnTe, and the purity of each metallic element is greater than or equal to 99.999%. Subsequently, the metallic elements are uniformly mixed and then transferred into a quartz tube, and flame sealing of the tube is carried out under a vacuum environment with an absolute vacuum degree less than or equal to 0.1 Pa by using a hydrogen-oxygen machine.
[0051] S2. Under vacuum conditions, the quartz tube after flame sealing in step S1 is placed in a box furnace, heated from room temperature to 1273 K within 8 hours, and held for 10 hours; after the holding ends, it is immediately quenched in cold water to room temperature to obtain an ingot. Under vacuum conditions, the ingot is subjected to high-temperature annealing. The high-temperature annealing process includes: within 6 hours, heating the quartz tube from room temperature to 950 K, holding for 3 days, and then cooling to room temperature.
[0052] S3. The ingot after high-temperature annealing in step S2 is sufficiently ground into powder, and then spark plasma sintering is carried out under a vacuum environment. The sintering temperature is 673 K, the pressure is 52 MPa, and the time is 10 minutes, thus obtaining the SnTe bulk thermoelectric material.
[0053] For the Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric materials with different W concentrations and composite of two metal compounds in Examples 1-6 above and the SnTe thermoelectric material in Comparative Example 1 are subjected to the following tests.
[0054] 1. Phase analysis Using an X-ray diffractometer (XRD) to perform phase analysis on the Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric materials with different W concentrations and composite of two metal compounds in Examples 1-6 above and the SnTe thermoelectric material in Comparative Example 1. The results are as Figure 1 shown, where the ordinate intensity represents the intensity of the diffraction peak, and the abscissa 2θ represents the angle of the diffraction peak.
[0055] Figure 1 In (a), the results show that the main phase of all samples is the SnTe structure. In addition, as Figure 1In (b), the diffraction peaks of the Cu2Te phase can be clearly observed at around 25°; at the same time, as Figure 1 shown in (c), the diffraction peaks of the In2Te3 phase can also be clearly observed between 41° and 42°. The appearance of these composite phases indicates that Cu2Te and In2Te3 form independent crystal phases in the SnTe matrix, rather than dissolving into the SnTe lattice. No impurity phase containing W was found in the diffraction pattern of the sample doped with W during XRD detection. It is speculated that this is because the content of W in the sample is small and does not reach the solid solubility of W. However, as the content of W (i.e., the value of X) increases, the overall diffraction peak shifts towards a lower angle, which means that the overall lattice parameter becomes larger. In the solid solution region, the increasing trend of the lattice parameter may be due to the smaller W atoms occupying the interstitial positions in the SnTe lattice, rather than being caused by replacing Sn atoms or filling the Sn vacancies in the lattice.
[0056] 2. Electrical property analysis The thermoelectric properties evaluation device (Beijing Coreo CTA-3) was used to test the electrical properties of the Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric materials with different W concentrations and the two metal compound composites in Examples 1-6 and the SnTe thermoelectric material in Comparative Example 1 under the temperature condition of 50 - 550 °C to obtain the corresponding electrical conductivity (σ) and Seebeck coefficient (S). The test results are shown in Figure 2 and Figure 3 respectively.
[0057] The results show that the increase in electrical conductivity is mainly due to the increase in the hole carrier concentration, which leads to an increase in the Seebeck coefficient. This can be attributed to the flat band structure and valence band convergence caused by W and the composite phase In2Te3. Although the increase in hole carrier concentration is not conducive to the Seebeck coefficient, overall, the Seebeck coefficient remains relatively excellent.
[0058] The power factor (PF) represents the electrical transport ability of the thermoelectric material. As shown in Figure 4 , the vertical coordinate PF represents the power factor, and the horizontal coordinate T represents the temperature. Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18The power factors are all higher than those of undoped SnTe thermoelectric materials. The incorporation of high-valence W into the sample generates additional charge carriers. This process reduces the formation energy of intrinsic Sn vacancies, thereby leading to an increase in the charge carrier concentration. For the composite phase Cu2Te, Cu2Te is a conductive phase, and its introduction aims to increase the total number of charge carriers to significantly enhance the electrical conductivity of the material. W doping can regulate the band structure, effectively merging the light hole valence band and the heavy hole band, enabling the Seebeck coefficient of the carriers at high temperatures to be maintained or even increased despite the increase in the carrier concentration. For In2Te3, the introduction of In2Te3 can further optimize the band flattening effect and promote the merging of the empty valence bands. This band optimization increases the effective mass of the carriers, thereby increasing the Seebeck coefficient. Under the coupled action of these parameters, ultimately Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The power factor of the thermoelectric material has been greatly improved within the test range, demonstrating Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The thermoelectric material has good electrical transport properties.
[0059] 3. Microstructural analysis Analyze the microstructure of the Sn 2.78 W 0.12 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric material in Example 5. Figure 5 In (a) is the transmission electron microscope photograph of the Sn 2.78 W 0.12 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric material. Figure 5 As shown in (b), after measurement, the lattice fringe with an interplanar spacing d = 3.59 Å corresponds to the (006) plane of Cu2Te. Figure 5 As shown in (c), after measurement, the lattice fringe with an interplanar spacing d = 2.208 Å corresponds to the (123) plane of WTe2. Figure 5 As shown in (d), after measurement, the lattice fringe with an interplanar spacing d = 2.18 Å corresponds to the (822) plane of In2Te3. Figure 5As shown in (e), the measured lattice fringe with an interplanar spacing d = 3.168 Å corresponds to the (200) plane of SnTe. Figure 5 As shown in (e), the interplanar spacing of the SnTe (200) plane is 3.168 Å. In addition, the Figure 5 selected SnTe region in (f) was subjected to an inverse fast Fourier transform, Figure 5 and (g) reveals the presence of a large number of dislocations and lattice distortions in the SnTe matrix, which are caused by the size and mass differences between the introduced foreign atoms and the matrix.
[0060] 4. Thermal Conductivity Test The thermal conductivities of the Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric materials with different W concentrations and the composite of two metal compounds in Examples 1 - 6 and the SnTe thermoelectric material of Comparative Example 1 were tested at temperatures ranging from 50 - 550 °C. The thermal conductivities (κ tot ) of different thermoelectric materials vary with temperature as Figure 6 shown. The total thermal conductivity (κ 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 ) of all Sn tot thermoelectric materials decreases with increasing W concentration, and the total thermal conductivities of all composite and doped - composite thermoelectric materials are lower than that of the intrinsic SnTe thermoelectric material. The multi - sized microstructural defects (nano - precipitates and lattice distortions) in the SnTe matrix enhance the phonon - phonon and phonon - defect scattering effects, significantly suppressing the lattice thermal conductivity. By testing the electrical and thermal conductivities, the dimensionless thermoelectric figure of merit ZT of the Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric materials can be calculated, as Figures 7 - 8 shown. Due to the significant increase in the power factor and the decrease in the total thermal conductivity over the entire temperature range, the average ZT values of all Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 thermoelectric materials in the test temperature range are significantly improved. Sn 2.9-X WX Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The average ZT value of the thermoelectric material reaches 0.313 within 323 - 823K, which is about 149.7% higher than that of the undoped - composite SnTe thermoelectric material. Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The increase in the average ZT value of the thermoelectric material within the working temperature range has practical significance for improving the conversion efficiency of thermoelectric devices.
[0061] Among them, Sn 2.78 W 0.12 Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 The average power factor of the thermoelectric material within 323 - 823K is 16.96 μWcm -1 K -2 , and the average ZT value reaches 0.31. Compared with the undoped - composite SnTe thermoelectric material, they are increased by 96.8% and 149.7% respectively, that is, the thermoelectric performance of the SnTe - based thermoelectric material is greatly improved.
[0062] It should be understood that the application of the present invention is not limited to the above examples. For those of ordinary skill in the art, it can be improved or transformed according to the above description, and all these improvements and transformations should fall within the protection scope of the appended claims of the present invention.
Claims
1. A preparation method of SnTe-based thermoelectric materials, characterized in that The SnTe-based thermoelectric material is composed of tungsten-doped SnTe and composites of In2Te3 and Cu2Te, and the SnTe-based thermoelectric material is denoted as Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 , where x = 0 to 0.15 and x does not take 0; The preparation method of the SnTe-based thermoelectric material includes the steps: S1. In an inert gas environment, according to the chemical formula Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 Mixing Te, Sn, In, Cu and W in a stoichiometric ratio to obtain a mixed raw material, and vacuum packaging the mixed raw material; S2. Performing a melting reaction on the vacuum-sealed mixed raw materials to obtain an ingot, and annealing the ingot; S3. After grinding the annealed ingot into powder, performing spark plasma sintering to obtain the SnTe-based thermoelectric material.
2. The preparation method of the SnTe-based thermoelectric material according to claim 1, characterized in that, In step S1, the purities of the elemental Te, elemental Sn, elemental In, elemental Cu, and elemental W are respectively greater than or equal to 99.999%; The step of vacuum-sealing the mixed raw materials specifically includes: transferring the mixed raw materials into a quartz tube and sealing the quartz tube by using a hydrogen-oxygen flame in a vacuum environment.
3. The preparation method of the SnTe-based thermoelectric material according to claim 2, wherein, In step S2, the process conditions of the melting reaction include: heating the quartz tube from room temperature to 1200 - 1300K within 6 - 8 hours, and holding for 8 - 12 hours; after the holding is completed, quenching the quartz tube in supersaturated salt water at room temperature.
4. The preparation method of the SnTe-based thermoelectric material according to claim 3, wherein, The process conditions of the melting reaction are: heating the quartz tube from room temperature to 1273K within 8 hours, and holding for 10 hours; after the holding is completed, quenching the quartz tube in supersaturated salt water at room temperature.
5. The preparation method of the SnTe-based thermoelectric material according to claim 1, characterized in that, In step S2, the process conditions of the annealing treatment include: heating the ingot to 923 - 975K within 4 - 6 hours, holding for 1 - 3 days, and then cooling to room temperature.
6. The preparation method of the SnTe-based thermoelectric material according to claim 5, characterized in that, The process conditions of the annealing treatment are: heating the ingot to 950K within 6 hours, holding for 3 days, and then cooling to room temperature.
7. The preparation method of the SnTe-based thermoelectric material according to claim 1, characterized in that, In step S3, the process conditions of the spark plasma sintering include: performing sintering in a vacuum environment within a temperature range of 600 - 700K under a pressure of 50 - 60MPa, and the sintering time is 5 - 10 minutes.
8. The preparation method of the SnTe-based thermoelectric material according to claim 7, characterized in that, The process conditions of the spark plasma sintering are: performing at a temperature of 673K and a pressure of 52MPa in a vacuum environment, and the sintering time is 10 minutes.
9. A SnTe-based thermoelectric material, characterized in that, The SnTe-based thermoelectric material is prepared by using the preparation method of the SnTe-based thermoelectric material according to any one of claims 1 - 8.
10. A SnTe-based thermoelectric material, characterized in that, The SnTe-based thermoelectric material is composed of tungsten-doped SnTe and composites of In2Te3 and Cu2Te, and the SnTe-based thermoelectric material is denoted as Sn 2.9-X W X Te 2.9 -(In2Te3) 0.03 -(Cu2Te) 0.18 , where x = 0 to 0.15 and x does not take 0.
Citation Information
Patent Citations
Preparation method for SnTe thermoelectric materials with high output power density and energy conversion efficiency
CN109585639A
High-performance tungsten-doped SnTe-based thermoelectric material and preparation method thereof
CN116873880A